Effects of angiotensin 1-7 on the actions of angiotensin II in the renal and mesenteric vasculature of hypertensive and streptozotocin-induced diabetic rats - Dharmani, M.; Mustafa, Mohd Rais; Achike, F.I.; Sim, M.K. (Elsevier, 2007)
Angiotensin 1-7, a heptapeptide derived from metabolism of either angiotensin I or angiotensin II, is a biologically active peptide of the renin– angiotensin system. The present study investigated the effect of angiotensin 1-7 on the vasopressor action of angiotensin II in the renal and mesenteric vasculature of Wistar-Kyoto (WKY) rats, spontaneously hypertensive rats (SHR) and streptozotocin induced diabetic rats. Angiotensin II-induced dose-dependent vasoconstrictions in the renal vasculature. The pressor response was enhanced in the SHR and reduced in the streptozotocin-diabetic rat compared to WKY rats. Angiotensin 1-7 attenuated the angiotensin II pressor responses in the renal vasculature of WKY and SHR rats. However, the ability to reduce angiotensin II response was diminished in diabetic-induced rat kidneys. The effect of angiotensin 1-7 was not inhibited by 1-[(4-(Dimethylamino)3-methylphenyl] methyl]-5-(diphenylacetyl)-4,5,6,7-tetrahydro-1H-imidazo[4,5-c] pyridine-6-carboxylic acid ditrifluoroacetate (PD123319), an angiotensin AT2 receptor antagonist. (D-ALA 7)-Angiotensin I/II (1-7) (D-ALA) (an angiotensin 1-7 receptor antagonist), indomethacin (a cyclo oxygenase inhibitor), and N ω -Nitro-L-Arginine Methyl Ester (L-NAME)(a nitric oxide synthetase inhibitor) abolished the attenuation by angiotensin 1-7 in both WKY rats and SHR, indicating that its action is mediated by angiotensin 1-7 receptor that is either coupled to the release of prostaglandins and/or nitric oxide. The vasopressor responses to angiotensin II in mesenteric vasculature bed was also dose-dependent but smaller in magnitude compared to the renal vasculature. The responses to angiotensin II were relatively smaller in SHR but no significant difference was observed between WKY and streptozotocin-induced diabetic rats. Angiotensin 1-7 attenuated the angiotensin II pressor responses in WKY, SHR and diabetic-induced mesenteric bed. The attenuation was observed at the lower concentrations of angiotensin II in WKY and diabetic-induced rats but at higher concentrations in SHR. Similar observation as in the renal vasculature was seen with PD123319, D-ALA, and L-NAME. Indomethacin reversed the attenuation by angiotensin 1-7 only in the SHR mesenteric vascular bed. The present findings support the regulatory role of angiotensin 1-7 in the renal and mesenteric vasculature, which is differentially altered in hypertension and diabetes.